Governance Practices in Platform Ecosystems: Navigating Tensions Between Cocreated Value and Governance Costs - Huber, Thomas L.; Kude, Thomas; Dibbern, Jens (Information Systems Research, 2017)
Based on an exploratory multiple-case study in two platform ecosystems, we develop a process theory that explains how and why different ways of practicing ecosystem-wide governance are more or less successful in navigating the tension between cocreated value and governance costs. Our process theory shows that how ecosystem-wide rules and values are practiced considerably varies and changes over time. Initially, governance practices follow ecosystem-wide rules; if and how practices shift toward going beyond the rules hinges on specific necessary conditions. Irrespective of which governance route is taken, the tension between cocreated value and governance costs is more successfully addressed if practices are sensitive to ecosystem-wide values. The online appendix is available at https://doi.org/10.1287/isre.2017.0701 .